Лексические аспекты языковой игры в русском языке - Dubichynskyi, Volodymyr (Studia Rossica Posnaniensia, 2019)
Language game can take place on different language levels: phonetic, graphical, lexical-semantic, word-formative, morphological, syntax, and even pragmatics, stylistics etc. In the given article the lexical aspect of the language game is considered. Many creative language potencies are revealed most fully and brightly on the lexical-semantic level. Separate attention is paid to entimological units – lexical units which are described in the entimological dictionaries; as well as to the so called “anti-proverbs” – abnormal paremiological units.